Grand canonical simulations of hard-disk systems by simulated tempering - Mecke, Klaus; et al. (International Journal of Modern Physics C, 2004)
The melting transition of hard disks in two dimensions is still an unsolved problem and improved simulation algorithms may be helpful for its investigation. We suggest the application of simulating tempering for grand canonical hard-disk systems as an efficient alternative to the commonly-used Monte Carlo algorithms for canonical systems. This approach allows the direct study of the packing fraction as a function of the chemical potential even in the vicinity of the melting transition. Furthermore, estimates of several spatial characteristics including pair correlation function are studied in order to test the accuracy of the method and to analyze the melting transition in hard-disk systems. Our results seem to show that there is a weak first-order phase transition.
Keywords: hard-disk model; phase transition; metropolis hastings; simulated tempering